The Influence of Clothing Logo Color on Consumers’ Green Purchase Intention (Journal of Fiber Bioengineering and Informatics, 2024)
As a visual symbol of information, brand identity influences consumers’ perception of brand imageand their purchase intention. However, few literatures have examined the influence of brand identitycolor on consumers’ purchase intention. The present study takes the green brand logo of clothing asa stimulus material to explore the green symbol of its color and the influence of consumers’ greenconsumption intention. The results show that (1) the color of clothing brand logo has a significantimpact on consumers’ green consumption intention. Consumers have the strongest purchase intentionaroused by green clothing brand logos, and the weakest purchase intention aroused by red and purpleclothing brand logos. (2) Consumers have the strongest purchase intention provoked by dark-coloredclothing brand logos, and the weakest purchase intention provoked by light-colored clothing brand logos;(3) Green purchase intention is highly correlated with the symbol of clothing brand logo color.